2019
DOI: 10.1101/693275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for a unitary structure of spatial cognition beyond general intelligence

Abstract: Performance in everyday spatial orientation tasks (e.g. map reading and navigation) has been considered functionally separate from performance on more abstract object-based spatial abilities (e.g. mental rotation and visualization). However, evidence remains scarce and unsystematic. With a novel gamified battery, we assessed six tests of spatial orientation in a virtual environment and examined their association with ten object-based spatial tests, as well as their links to general cognitive ability (g). We fu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…e unifactorial structure of spatial ability was further demonstrated in another study that examined 16 measures of spatial ability in a UK sample (Malanchini et al, 2019). In this study, three factors emerged: navigation, object manipulation, and visualization; these in turn loaded strongly on a general factor of spatial ability.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…e unifactorial structure of spatial ability was further demonstrated in another study that examined 16 measures of spatial ability in a UK sample (Malanchini et al, 2019). In this study, three factors emerged: navigation, object manipulation, and visualization; these in turn loaded strongly on a general factor of spatial ability.…”
Section: Introductionmentioning
confidence: 52%
“…However, several recent studies (Esipenko et al, 2018;Likhanov et al, 2018;Malanchini et al, 2019;Rimfeld et al, 2017) showed that spatial ability might have a unifactorial rather than multidimensional structure. For example, research has shown that the 10 spatial ability tests which form a King's Challenge test battery (Rimfeld et al, 2017), constitute a single factor in British and Russian samples, explaining 42 and 40 percent of overall variance in spatial ability measures, respectively (Likhanov et al, 2018;Rimfeld et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…56 Although this model has not been tested using PGS, researchers using quantitative genetic methods found that a shared genetic factor accounted for the association between various measures of self-regulation and academic outcomes. 57,58 Genetic influences are not deterministic, as many children with a low EA PGS perform well academically. Instead, associations between PGS and outcomes of interest reflect complex transactions between genes and the environment.…”
Section: Discussionmentioning
confidence: 99%